Pré-tratamento de casca de arroz utilizando líquido iônico [C16MIM][Br] - Bohn, Patrícia Daniela (2019)
Rice husk, an agricultural residue, is a cellulose rich material which present potential to produce second generation ethanol, however, due its recalcitrant structure related to the presence of lignin and silica, a pretreatment is necessary to broke down this structure. Many types of pretreatment could be applied, besides that ionic liquids pretreatment have been studied, because are considered green solvents which present characteristics as such biodegradability. In this study, rice husk was pretreated with ionic liquid 1-hexadecyl-3-methylimidazolium bromide [C16MIM][Br] and the influence of ionic liquid:water ratio and temperature in reducing sugars yield after enzymatic hydrolysis was investigated using experimental design. Morphological and structural changes by scanning electron microscopy (SEM), x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) were evaluated. Experimental design shows a positive influence of temperature in the pretreatment whereas ionic liquid:water ratio was not significance at the range evaluated. Validation assay at 180°C, 1:20 ionic liquid:water ratio, 10% of biomass for 12 hours was performed, an improvement in reducing sugars yield (38.04%) was observed in comparison with the untreated (0.18%). Moreover, a dissolution of biomass up to 60% was obtained after the pretreatment, which is related to removal of compounds, which were identified by characterization analysis, showing changes in rice husk structure as such an exposed and more accessible surface for the enzymes and removal of amorphous portions (such as lignin and hemicellulose). The [C16MIM][Br] ionic liquid was effective on rice husk pretreatment, resulting in higher reducing sugars yield comparing to the yield of released sugar from rice husk without pretreatment, it could be used as alternative in the lignocellulosic biomass pretreatment to obtain fermentable sugars.